2015
DOI: 10.3168/jds.2015-9649
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the nutritional regulation of milk fat secretion and composition in cows and goats

Abstract: A study with 2 ruminant species (goats and cows) with inherent differences in lipid metabolism was performed to test the hypothesis that milk fat depression (MFD) due to marine lipid supplements or diets containing high amounts of starch and plant oil is caused by different mechanisms and that each ruminant species responds differently. Cows and goats were allocated to 1 of 3 groups (4 cows and 5 goats per group) and fed diets containing no additional oil (control) or supplemented with fish oil (FO) or sunflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
115
9
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(164 citation statements)
references
References 50 publications
(137 reference statements)
36
115
9
2
Order By: Relevance
“…Faced with the absence of direct interspecies comparisons of diet-induced MFD among these species, a comparative study with lactating cows and goats was undertaken to determine the mechanisms underlying the differences of mammary lipogenic responses between these ruminant species. From this study, animal performance responses including milk fat yield, FA composition (Toral et al, 2015), and rumen metabolism (Toral et al, 2016) were reported and revealed relevant interspecies differences and species-by-diet interactions. The present study aimed to provide further insight into the mechanisms regulating mammary lipogenesis in ruminants.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Faced with the absence of direct interspecies comparisons of diet-induced MFD among these species, a comparative study with lactating cows and goats was undertaken to determine the mechanisms underlying the differences of mammary lipogenic responses between these ruminant species. From this study, animal performance responses including milk fat yield, FA composition (Toral et al, 2015), and rumen metabolism (Toral et al, 2016) were reported and revealed relevant interspecies differences and species-by-diet interactions. The present study aimed to provide further insight into the mechanisms regulating mammary lipogenesis in ruminants.…”
Section: Introductionmentioning
confidence: 92%
“…The details of the experimental design have been described in Toral et al (2015). Briefly, 12 multiparous nonpregnant Holstein cows and 15 multiparous nonpregnant Alpine goats were allocated to 1 of 3 groups (4 cows and 5 goats each) and used in a replicated 3 × 3 Latin square to test the effects of 3 treatments during three 25-d experimental periods.…”
Section: Animals Experimental Design Diets and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Cow cattle are the most significant milk producer in the world, but in recent years there has been a considerable increase in the production and industrialisation of goat milk [1], and there is a growing interest in research and investment in goat milk in several countries, mainly due to its attractive nutrient content. Regarding that, goat milk has lower lactose content and a higher concentration of total solids (mostly proteins and fats) and nutrients than cow milk [3]- [6]. Fat from goat milk influences positively on sensory properties of food products, more than that from cow milk [5].…”
Section: Introductionmentioning
confidence: 99%